La Generación de herramientas genómicas para la investigación y determinación de factores de riesgo genético de obesidad en la población mexicana - Hernández Rosas, Fabiola; De león Bautista, Mercedes Piedad; Orozco Hernández, Erika; Navarro-Vidal, E.; Martínez Chacón, Armando J (Memorias del Congreso Nacional de Ingeniería Biomédica, 2021)
Genetic predisposition has been shown to play a key role in obesity. Genome-wide association studies (GWAS) have identified multiple loci linked with obesity in various ethnic groups. However, their contribution to obesity in the Mexican population is largely unknown. The aim of this study was to determine if there is evidence of an association between 52 candidate polymorphisms (SNPs) and the susceptibility to develop overweight and obesity in Mexican adults. To achieve this goal, we developed a multiplexed genetic panel to identify 52 SNPs per patient by MALDI-TOF mass spectrometry-based SNP genotyping. To test the genetic panel, we collected DNA samples from the whole blood of 1117 patients from central Mexico. In our study, we found 8 loci associated with the obesity phenotype and the increase in BMI in the Mexican population in genes that encode proteins: Leptin, LINGO2, AP2B transcription factor, and FTO. The results of the work will be used in later stages for the study of specific therapeutic targets to reduce obesity and for the investigation of new genetic factors that could be predictive in the Mexican population.